(untitled) (Nepalese Journal of Radiology, 2013)
Congenital absence of pericardium is rare. Pericardial defects can be complete or partial. Partial pericardial defect may be symptomatic. We report a rare case of partial pericardial defect in an asymptomatic patient which was suggested by chest radiograph and confirmed by computed tomography and brief review of literature is also presented. Nepalese Journal of Radiology; Vol. 2; Issue 2; July-Dec. 2012; 65-68 DOI: http://dx.doi.org/10.3126/njr.v2i2.7688